Ex-Ante Impact Assessment of water policy reform in Southeastern of Tunisia:: A CGE Approach - Arbi, Abdeladhim Mohamed; Chant, Lindsay; Abdallah, Akari; Mongi, Sghaier (Sustainability in Debate, 2011)
Located in the South-East of Tunisia, the Medenine governorate is characterised by an arid climate. The water scarcity was accentuated by the growing demand from different economic sectors. Thereby the inter-sectorial competition for water, mainly between tourism and agriculture, presents a major problem. This area of socio-economic and geopolitical interest has profited from various programmes of development; in particular, multiple water policy reforms. Despite of the early public intervention, since 80s, the ex-ante integrated impact assessment (IIA) of water policies reform needs more investigation in Tunisian arid regions. Using a Computable general equilibrium model we have assessed the economywide impact of water policies reform that consists of providing higher quantity water to the different economic sectors. The central aims are to outline the Social Accounting Matrix (SAM) building procedure, describe the policy options and present the preliminary results. Model results show that providing more non-conventional water to tourism and agriculture sectors has positive impacts on regional economy. Meanwhile, the results should be analysed with caution given the various limitations of the work that should be enhanced. This work was carried out in the framework of Land Use Policies and Sustainable Development on developing countries (LUPIS) project (Reidsma et al., 2011).